Jejaring Kerja Organisasi dalam Pencegahan HIV/AIDS di Kabupaten Kediri - Andreka Anugrah Adam Pratama (Jurnal Administrasi Publik, 2015)
Abstract: The Working Network of Organization in Preventing HIV/AIDS in Kediri Disctrict. Networking or "network" has become an important concept in the study of the science of public administration. Network or network this is a structure which contained a variety of connected actor. The purpose of this study is to describe and analyse organization networks in preventing HIV/AIDS in Kediri District. The study found various types of organizational network in HIV/AIDS prevention programs. Results of social network analysis show that few actors have key roles within those programs. For example, District Health Agency and KPAD have main role in dissemination HIV/AIDS prevention. However, it shows that among important actors did not involved within the programs indicating lack of collaboration among actors in preventing HIV/AIDS in Kediri. Thus in order for HIV/AIDS prevention programs in the District of Kediri was able to walk with a maximum then need for expansion of the actors with important actors involved in each HIV/AIDS prevention programs in the District of Kediri. Keyword : working network, HIV/AIDS prevention, Kediri Abstrak:. Jejaring Kerja Organisasi dalam Pencegahan HIV/AIDS di Kabupaten Kediri. Jejaring atau â€œnetworkâ€ telah menjadi sebuah konsep terpenting dalam kajian ilmu administrasi publik. Jejaring atau network ini merupakan sebuah struktur yang didalamnya terdapat berbagai aktor yang saling terhubung. Penelitian ini bertujuan untuk menjelaskan dan menganalisis jejaring kerja organisasi dalam pencegahan HIV/AIDS di Kabupaten Kediri. Hasil penelitian ini menemukan bahwa pola jejaring yang beragam dalam setiap program pencegahan HIV/AIDS di Kabupaten Kediri. Hasil analisis jejaring sosial menunjukkan beberapa aktor kunci dalam setiap program pencegahan HIV/AIDS di Kabupaten Kediri. Misalnya Dinas Kesehatan dan KPAD memegang peranan penting dalam program sosialisasi HIV/AIDS. Penelitian ini menemukan belum adanya kerjasama yang luas dalam beberapa program-program pencegahan HIV/AIDS di Kabupaten Kediri. Kurang adanya kerjasama yang luas ini menjadi salahsatu penyebab upaya pencegahan HIV/AIDS yang belum maksimal selama ini. Maka dari itu agar program pencegahan HIV/AIDS di Kabupaten Kediri bisa berjalan dengan maksimal maka perlu adanya perluasan aktor dengan melibatkan aktor-aktor penting dalam masing-masing program pencegahan HIV/AIDS di Kabupaten Kediri. Kata Kunci : jejaring ikerja, pencegahan HIV/AIDS, Kediri